Diversity work in community sport organizations: Commitment, resistance and institutional change. (May 2018) - Spaaij, Ramón; Magee, Jonathan; Farquharson, Karen; Gorman, Sean; Jeanes, Ruth; Lusher, Dean; Storr, Ryan
Diversity is a key term used in a range of public and private organizations to describe institutional goals, values and practices. Sport is a prominent social institution where the language of diversity is frequently and positively used; yet, this rhetoric does not necessarily translate into actual practice within sport organizations. This paper critically examines diversity work in community sports clubs. Drawing upon qualitative research at 31 amateur sports clubs in Australia, the findings show that diversity work in community sport organizations is often haphazard and accidental, rather than a strategic response or adaptation to policy. This paper concludes that while individual champions are critical to the promotion of diversity, persistent tensions and resistance arise when they seek to translate the language of diversity into institutional practice and culture change.